"The world we live in now": A qualitative investigation into parents', teachers', and children's perceptions of social networking site use. (12th August 2021) - Hayes, Beatrice; James, Alana; Barn, Ravinder; Watling, Dawn
Abstract : Background: Younger children are increasingly using social networking sites (SNS; Ofcom, Children and Parents: Media Use and Attitudes Report, 2019, https://www.ofcom.org.uk/__data/assets/pdf_file/0020/108182/children‐parents‐media‐use‐attitudes‐2017.pdf ). In doing so, they may experience both benefits (e.g., enhanced social capital) and risks (e.g., cyberbullying). Parents and teachers play an important role in shaping children's perceptions via internet mediation behaviours (Livingstone et al ., 2017, J. Commun., 67, 82). Aims: An understanding of both children's and adults' perceptions of the risks and benefits of SNS use within the home and school contexts is limited within current literature. This study explored parents', teachers', and children's perceptions of the risks and benefits of SNS use and how adults mediate this. Sample(s): A sample of 42 participants, including 13 parents (aged 28–48), 14 teachers (aged 26–54), and 15 children (aged 7–12), participated within this study. Methods: Participants took part in one‐to‐one semi‐structured interviews exploring SNS use and risk and benefit perceptions, as well as internet mediation behaviours with adult participants. Results: Findings highlight bonding social capital as the main benefit. Children recognize stranger danger as a risk but fail to perceive the wider online risks (e.g., cyberbullying). Parents' and teachers' restrictive mediation behaviours are informed by perceptions of stranger danger, safeguarding, and children lacking online responsibility. Conclusions: Findings highlight the importance of shifting guidance from stranger danger to discussing the wider SNS risks, as well as the benefits; it is crucial for greater financial investment and policy to overcome barriers to e‐safety education.